BIG DATA: AN INDISPENSABLE RESOURCE FOR BUSINESS MANAGEMENT IN NIGERIA - Grace Aruoriwo-oghene Addah; Oghenenyerhowvo Shulammite OMOGBIYA (Indonesian Journal of Strategic Management, 2023)
Big Data opens up new business opportunities, and businesses can use it to gain a competitive advantage. New technologies are expected to be used in business management, particularly in data exchange, document recognition, communication and text recognition, receipt and payment transactions, and excel replacement. Big Data has evolved to account for the rapidly increasing quantities of digital information systems generated, the effort required to create information that can be analyzed, and the actual use of that data as capital to increase efficiency and improve business management decision-making. Against this backdrop, this research investigates the importance of Big Data in business management in Nigeria. In order to gather data for this study, relevant information was extracted from books, conference papers, public records, journals, and other sources. This study comes to the conclusion that efficient data use is becoming the foundation of competition; Big Data fundamentally alters how companies compete and function. Businesses in Nigeria that make the necessary investments and successfully extract value from their data will have a clear advantage over their rivals. Almost every aspect of business, from research and development to sales, marketing, and supply-chain management, including new growth opportunities, has the potential to be transformed by Big Data. The study among others recommends strategies to optimize the benefits of Big Data for business value in Nigeria. This study is significant because it investigates a problem in a largely unexplored area of research in Nigeria. As a result, this research adds to the body of knowledge on the role of Big Data in business management in Nigeria.